Analysis of monocyte and lymphocyte counts of TBDC patients taking anti-TBC drugs - Susanti, Eka; Sugiono, Sugiono; Kamilla, Laila (ELECTRON (Journal of Science and Technology), 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that attacks the lungs and spreads through the air. Monocytes and lymphocytes play an important role in the immune response to TB. Changes in their numbers can reflect the immune response and treatment effectiveness. Monitoring patients during treatment provides insight into disease progression and therapy response. This study aims to analyze the number of monocytes and lymphocytes in TB patients taking anti-tuberculosis drugs at Puskesmas Ledo, Bengkayang Regency. The study was descriptive quantitative to describe the number of monocytes and lymphocytes. The population was all TB patients undergoing treatment in the working area of Puskesmas Ledo, with total sampling technique and the number of respondents as many as 30 people. From the results of the study, 21 respondents had high monocyte counts: 8 in the early phase of treatment and 13 in the advanced phase. Meanwhile, 9 respondents had non-high monocyte counts, consisting of 4 in the initial phase and 5 in the continuation phase. Of the total respondents, 3 people had high lymphocyte counts, namely 2 in the initial phase and 1 in the continuation phase, while 27 had non-high lymphocyte counts, consisting of 10 in the initial phase and 17 in the continuation phase. In conclusion, high monocyte counts were more common in the continuation phase (61.9%), while high lymphocyte counts were more common in the early phase (66.7%).